Analisis Pengaruh Variabel Makroekonomi Dan Mikroekonomi Terhadap Harga Saham (Studi Pada Bank Mandiri Periode 2006-2015) - Junaied Ibrahim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to find out the impact of Exchange Rate, Interest Rate, Return on Asset (ROA) and BOPO to Stock Price of Mandiri Bank. The method of data analysis was multiple regression models and used secondary data quarterly period 2006 to 2015. The empirical results showed that exchange rate is significant have a positive effect on stock price of Mandiri Bank, while Bopo is significant have a negative effect on stocek price of Mandiri Bank. However, Interest Rate and Return on Asset (ROA) have no effect to stock price on Mandiri Bank. Keywords: Exchange Rate, Interest Rate, Return on Asset, Bopo, and Stock Price.